Jeunes-Turcs et Hellénisme : de l’enthousiasme à la réalité - Alkisti Sofou (Cahiers Balkaniques)
Relations, tensions, conflicts between the Greek and the Young Turks from 1908 to 1914: the revolution of the Young Turks was a turning point in the history of hellenism. Many Rum, despite some dissenting voices, believed that the new regime would lay the groundwork for collaboration of the people of the Empire to their advantage. The progressive hardening of the Young Turks policy gradually dispelled such illusions. After defeats and the Balkan Wars, the Turkish government turned to a more nationalistic policy: boycotting businesses owned by Christian population and violently expulsion of the Rums from the Asia Minor coast, even before the outbreak of the First World War.